2022
DOI: 10.3390/agronomy12061284
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Use Efficiency in Durum Wheat (Triticum durum Desf.) Grown under Semiarid Conditions in Algeria

Abstract: The proper and sustainable management of nitrogen fertilization is one of the most common problems of cereal cultivation in semiarid regions, which are characterized by a wide variability in climatic conditions. The current work was conducted to evaluate the effects of nitrogen fertilization on the agronomic and economic aspects of durum wheat cultivated under rainfed semiarid conditions in Algeria and to determine the most efficient nitrogen use efficiency (NUE) among four genotypes that are widespread in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Bektash and Naes (2016) found significant differences among the different bread wheat lines for biological yield while studying several genotypes, with the wheat line 12-S recorded with the highest grain yield (16.96 t ha -1 ). Benchelali et al (2022) found in their study of four durum wheat (Triticum durum Desf.) genotypes with four nitrogen levels (0, 40, 80, and 120 kg N ha -1 ) over three seasons, the highest NUE (19.06) appeared at fertilizer level 40 kg N ha -1 , and the highest fertilizer level (120 kg N ha -1 ) emerged with the less NUE value (10.91).…”
Section: Introductionmentioning
confidence: 94%
“…Bektash and Naes (2016) found significant differences among the different bread wheat lines for biological yield while studying several genotypes, with the wheat line 12-S recorded with the highest grain yield (16.96 t ha -1 ). Benchelali et al (2022) found in their study of four durum wheat (Triticum durum Desf.) genotypes with four nitrogen levels (0, 40, 80, and 120 kg N ha -1 ) over three seasons, the highest NUE (19.06) appeared at fertilizer level 40 kg N ha -1 , and the highest fertilizer level (120 kg N ha -1 ) emerged with the less NUE value (10.91).…”
Section: Introductionmentioning
confidence: 94%